2011
DOI: 10.1007/s10585-011-9433-5
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4/CXCL12 expression profile is associated with tumor microenvironment and clinical outcome of liver metastases of colorectal cancer

Abstract: Interaction between CXCR4 and CXCL12 plays a role in tumor progression. The present study examined CXCR4, CXCL12 and CD133 expression in liver metastases of colorectal cancer (CLM) and determined whether the expression profiles affect the tumor microenvironment and thus progression, and whether they could serve as a prognostic marker for survival. Liver metastases of colorectal cancer collected from 92 patients were evaluated by CXCR4, CXCL12 and CD133 immunohistochemistry and clinicopathological data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
2
29
0
1
Order By: Relevance
“…Chemokines and their receptors, can be used by cancer cells in order to modulate the host microenvironment and also ease cancer progression [82,83]. Chemokines and their receptors have been shown to regulate various metastatic and advanced cancers, with interleukin-8 (IL-8) and its receptor CXCR2 being two of the most significantly upregulated chemokines in colon cancer [84].…”
Section: Cxcr4/cxcl12 Axis and The Crlm Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…Chemokines and their receptors, can be used by cancer cells in order to modulate the host microenvironment and also ease cancer progression [82,83]. Chemokines and their receptors have been shown to regulate various metastatic and advanced cancers, with interleukin-8 (IL-8) and its receptor CXCR2 being two of the most significantly upregulated chemokines in colon cancer [84].…”
Section: Cxcr4/cxcl12 Axis and The Crlm Pathwaymentioning
confidence: 99%
“…CXCR4, an established inducer of colorectal cancer progression, has been found to be significantly higher in liver metastases than in primary colorectal cancer [82,85]. The CXCR4 ligand, CXCL12/stromal-derived factor-1 (SDF-1), is also linked to tumour progression and accumulates in CD133-positive tumour cells [86][87][88]; the hypothesis is that there is interaction between CXCR4 and CXCL12 expression, highlighting this as causing tumours to proliferate, migrate, and invade other organs.…”
Section: Cxcr4/cxcl12 Axis and The Crlm Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a recent study found that CXCR4/CXCL12 plays a significant role in pancreatic cancer organ-specific metastasis [46]. However, in renal cancer, the incidence of CXCR4 expression is lower [47,48] than in colorectal [49,50] or pancreatic cancers [51,52], suggesting that this chemokine system may not be the primary driver of the skin-selective homing mechanism.…”
Section: Mechanisms Of Organ Selectivitymentioning
confidence: 99%